2021
DOI: 10.1186/s12974-021-02197-w
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury results in unique microglial and astrocyte transcriptomes enriched for type I interferon response

Abstract: Background Traumatic brain injury (TBI) is a leading cause of death and disability that lacks neuroprotective therapies. Following a TBI, secondary injury response pathways are activated and contribute to ongoing neurodegeneration. Microglia and astrocytes are critical neuroimmune modulators with early and persistent reactivity following a TBI. Although histologic glial reactivity is well established, a precise understanding of microglia and astrocyte function following trauma remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 52 publications
(60 reference statements)
5
44
1
Order By: Relevance
“…We have found greater transcriptional activation of microglia specific markers, compared to astrocytes, which has been shown in vivo rodent injury studies as well (31). Some of the markers were not detected in our model (some examples are IFI209, OASL2, IFI27I2A, IRF9, and H2-Q4), due to species differences, and limitations of our model (lack of macrophages, blood vessels, and other factors) (31). Among upregulated genes in astrocytes were GBP3, IFIT3; and downregulated MAFB.…”
Section: Mitochondria Dysregulation-induced Neurodegeneration and Inf...supporting
confidence: 73%
“…We have found greater transcriptional activation of microglia specific markers, compared to astrocytes, which has been shown in vivo rodent injury studies as well (31). Some of the markers were not detected in our model (some examples are IFI209, OASL2, IFI27I2A, IRF9, and H2-Q4), due to species differences, and limitations of our model (lack of macrophages, blood vessels, and other factors) (31). Among upregulated genes in astrocytes were GBP3, IFIT3; and downregulated MAFB.…”
Section: Mitochondria Dysregulation-induced Neurodegeneration and Inf...supporting
confidence: 73%
“…Following mTBI, the microglia only proliferated in WT mice CA1 hippocampus on both the ipsilateral and contralateral sides. Even though microglia were increased only in WT mice after mTBI, we observed an increment in the activated (motile) and a reduction in the less activated (resting) microglia in both strains [ 47 ] on the ipsilateral side ( Figure 4 ). The observation that astrocytes and microglia increased also on the contralateral side indicates that the augmented gliosis occurring in the ipsilateral side is also seen in distant regions and may explain the loss of synaptic contacts [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using a CCI model in young adult mice indicates that neurons release IFN-b in response to TBI which leads to activation of colocalized microglia (101). In contrast, Karve and colleagues provided evidence that peripheral immune cells drive the IFN-I response in the brain following TBI (12), while another recent RNAseq study identified unique microglial and astrocyte transcriptomes enriched for IFN-I following lateral fluid percussion injury in mice (102). Almost all cell types in the body can produce IFN-I (103), and it is likely that all damaged cells release IFN-I in the brain following TBI.…”
Section: Discussionmentioning
confidence: 99%